2021
DOI: 10.5603/cj.a2021.0150
|View full text |Cite
|
Sign up to set email alerts
|

Mean platelet volume-to-platelet count ratio after elective cardiac surgical procedures is superior in reflecting platelets metabolic hyperactivity compared to other routine morphological platelet indices: A preliminary report

Abstract: Background Excessive metabolic excitation of platelets after cardiac procedures may be related to some adverse events but assessment of their metabolic activity is not routine. The purpose of this study was to evaluate which of the basic platelet morphological parameters best reflects their metabolic status. Methods The blood samples of 22 cardiac surgical patients (mean age of 62.3 ± 10.3 years) were taken before surgery (BS), and 1, 24 and 48 hours after the operation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…In addition to being the main cell that provides primary hemostasis for tissue healing, platelets mediate the release of cytokines so that other cells necessary for tissue healing migrate to the damaged area [21]. Platelets newly released from megakaryocytes tend to be larger than mature platelets [22]. Based on the view that PIs may reflect the activities of platelets, we planned our study to investigate the effects of PIs on mechanical complications of PD.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to being the main cell that provides primary hemostasis for tissue healing, platelets mediate the release of cytokines so that other cells necessary for tissue healing migrate to the damaged area [21]. Platelets newly released from megakaryocytes tend to be larger than mature platelets [22]. Based on the view that PIs may reflect the activities of platelets, we planned our study to investigate the effects of PIs on mechanical complications of PD.…”
Section: Discussionmentioning
confidence: 99%
“…The MPV/PC ratio has been investigated in the diagnosis, prognosis and risk characterization in various diseases, eg, myocardial infarction (MI), sepsis, and metabolic status of platelets in cardiac surgical patients. [13][14][15][30][31][32] Guenancia et al 33 suggested that a high MPV/PC ratio might help to identify acute MI patients at increased risk of inhospital ischemic stroke. To our knowledge, the association of the MPV/PC ratio and NVAF has not been reported till now.…”
mentioning
confidence: 99%